HOW CEO NARCISSISM AFFECTS THE FINANCIAL PERFORMANCE OF COMPANIES: A REVIEW - Dr. Sadiq jaafar kadhim Alataby; Dr. Bashaer Khudhair Abbas Alkhafaji (Journal Park Publishing, 2024)
Because CEO narcissism influences CEO behavior in many ways, it is an area of study with strategic implications and has significant implications for CEO behavior. The CEO's narcissism may be idealistic or harmful to the company's financial performance. Therefore, the problem of our research revolves around answering the following question: How does CEO narcissism affect the financial performance of companies? through a narrative analysis of the most important previous studies in various countries. Our research contributes scientific value by enhancing the scientific debate and showing that CEO narcissism is not all opportunism. Senior managers strive for better financial performance, while for others, their narcissism is negatively reflected in financial performance. The researchers recommend the necessity of activating strong supervision by setting specific standards and mechanisms for the CEO and enhancing partnership and cooperation in the executive management of the company, that is, working in a team spirit to ensure improving the company’s financial performance and achieving sustainability.
Keywords: CEO narcissism, financial performance.